The European crisis and migration to Germany: Expectations and the diversion of migration flows - Simone Bertoli; Herbert Brücker; Jesús Fernández-Huertas Moraga (Institute for the Study of Labor (IZA), 2013)
The analysis of how the economic crisis in Europe has reshaped migration flows faces two challenges: (i) the confounding influence of correlated changes in the attractiveness of alternative destinations, and (ii) the role of rapidly changing expectations about the evolution of the economic conditions in various countries. This paper addresses the first challenge by controlling for multilateral resistance to migration, and the second one by incorporating 10-year bond yields as an explanatory variable in a study of European bilateral migration flows to Germany between 2006 and 2012. We show that, while expectations and current economic conditions at origin are significant determinants of migration, diversion effects account for 78 percent of the observed increase in German gross migration inflows.
Keywords: F22; O15; J61; 330; international migration; multiple destinations; diversion; expectations